Diagnostic efficacy of serum procalcitonin, IL-6, IL-2, and D-dimer levels in an experimental acute appendicitis model - Sabahattin Destek; Vahit Onur Gül; Mustafa Öner Menteş; Ali Fuat Çiçek (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Acute appendicitis is the most frequent cause of acute abdomen emergency surgery. It continues to be a problem today due to delayed diagnosis and its high perforation rate. For this reason, diagnostic tests continue to be developed. In this experimental study, the diagnostic significance of blood procalcitonin (PCT), interleukin (IL)-6, IL-2, and D-dimer levels in an acute appendicitis model in rabbits was investigated. Materials and Methods: A total of five groups were included: control group, sham group, and three different acute appendicitis groups. In the appendicitis groups, the appendix was ligated by laparotomy, and the blood PCT, IL-6, IL-2, and D-dimer levels were measured at 12 (group 3), 24 (group 4), and 48 h (group 5). Then, an appendectomy was performed. Results: In the present study, PCT and IL-6 levels increased in parallel with the inflammation of the appendix in all groups and were found to be statistically significant. IL-2 and D-dimer values were higher in the groups diagnosed with appendicitis but were not statistically significant. Conclusion: In our experimental study, PCT and IL-6 levels were determined to be important in the early diagnosis of acute appendicitis, especially IL-6, and that these two parameters are more important markers than IL-2 and D-dimer. Cite this article as: Destek S, Gül VO, Menteş MÖ, Çiçek AF. Diagnostic efficacy of serum procalcitonin, IL-6, IL-2, and D-dimer levels in an experimental acute appendicitis model. Turk J Gastroenterol 2019; 30(7): 641-7.